Proprietary Trading and the Real Economy - Stefan Arping (Tinbergen Institute, 2013)
We embed proprietary trading into a model of bank lending. Opportunities to engage in purely speculative trading can harm the real economy. This is because banks, when devoting cheap but scarce deposits to lending rather than to gambling, must be compensated for giving up gambling rents. This makes corporate loans more costly, stifling real economic activity. Worse, gambling can crowd out lending, forcing firms to seek costly bond financing. By contrast, when trading is required for the provision of complementary banking services, banks may actually engage in too little trading. Ring-fencing trading can facilitate the efficient provision of banking services.
Keywords: G2; G3; 330; Proprietary Trading; Volcker Rule; Disintermediation; Shadow Banking; Depositor Preference; Safe Harbors; Covered Bonds; Ring-fencing; Financial Stability